2007
DOI: 10.1159/000099241
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Retrobulbar Vasculature to Hypercapnia in Primary Open-Angle Glaucoma and Ocular Hypertension

Abstract: Purpose: To evaluate the physiological effects of hypercapnia on the retrobulbar vasculature in ocular hypertension (OH) and open-angle glaucoma (OAG). Methods: Peak systolic velocity (PSV), end-diastolic velocity (EDV) and resistive index (RI) of the ophthalmic (OA) and central retinal arteries (CRA) were evaluated in 12 eyes with OH and 8 eyes with OAG using color Doppler imaging. Measurements were taken before and during hypercapnia. Results: Patients with OAG were found to have increased EDV (p < 0.035) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…Patients with ocular hypertension were found to have a normal vasodilatory response within the retrobulbar vasculature during hypercapnia resulting in increased volumetric blood flow to the retina while patients with glaucoma did not, suggesting there is vasospasm at or downstream from the central retinal artery, which may result in decreased volumetric blood flow to the retina. 104 This builds upon previous research by Harris et al that found that NTG patients had reversible vasospasm apparent in the retrobulbar blood vessels. …”
Section: Migrainessupporting
confidence: 70%
See 2 more Smart Citations
“…Patients with ocular hypertension were found to have a normal vasodilatory response within the retrobulbar vasculature during hypercapnia resulting in increased volumetric blood flow to the retina while patients with glaucoma did not, suggesting there is vasospasm at or downstream from the central retinal artery, which may result in decreased volumetric blood flow to the retina. 104 This builds upon previous research by Harris et al that found that NTG patients had reversible vasospasm apparent in the retrobulbar blood vessels. …”
Section: Migrainessupporting
confidence: 70%
“…11,125 In this capacity, the cerebral and ocular circulations may be related, and evidence suggests that systemic vascular regulatory dysfunction may also exist in NTG and POAG patients. 104,126 Furthermore, an ultrasound study of cerebral hemodynamics found diminished central visual function to be one manifestation of widespread cerebrovascular insufficiency in glaucoma. 127 The vascular dysfunction in the retrobulbar blood vessels measured by CDI may also appear as an observable vasospasm in certain glaucoma patients.…”
Section: Color Doppler Ultrasound Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Select glaucoma patients may have an observable vasospasm as evidence of vascular dysfunction in the retrobulbar blood vessels measured by CDI. 21 Vasospasm within the blood vessels supplying the optic nerve head (ONH) and retinal ganglion cells may cause increased loss of visual function and increased progression of glaucoma. 18,22 In patients with OAG, asymmetric glaucomatous visual fi eld loss was associated with asymmetric blood fl ow velocities in the central retinal and ophthalmic arteries.…”
Section: Color Doppler Ultrasound Imagingmentioning
confidence: 99%
“…Auch dies wurde als partielle Reversibilität einer relativen Vasokonstriktion bei Glaukompatienten interpretiert. Sines et al [27] berichteten über einen Anstieg der EDV der A. centralis retinae unter Hyperkapnie bei Patienten mit POWG, während die Blutfließgeschwindigkeiten der A. ophthalmica sogar sanken. Venkataraman et al [28] fanden hingegen eine verminderte Antwort der retinalen Gefäße und der Perfusion des Sehnervs mithilfe der Laserdoppler-Flowmetrie bei Patienten mit unbehandeltem und fortschreitendem POWG unter Hyperkapnie.…”
Section: Diskussionunclassified